Technology of stable transportation of combustion by-products in the framework of termal power plant "Pljevlja" by belt conveyors - Miljković Nikola; Živanović Miloš; Jovanović Nikola; Pavlović Zlatko; Stefanović Jelena (Bakar)
After the ecological reconstruction of the "Pljevlja" thermal power plant, ash and slag are produced as combustion by-products in amounts of 420.000 t and 70.000 t, while after desulphurization process, gypsum is obtained in the amount of 154.000 t. This paper deals with the transportation of all three materials by conveyors from the storage silo to the new material loading location within the thermal power plant.